The beginnings of cinema. Philosophical inquiries - Bastek, Adam (Hybris, 2016)
This article centres on the beginnings of the art of cinematography as viewed from a philosophical perspective. Every art form has its beginnings, and cinema is no exeption. Nevertheless, some film theorists, as Jean Louis Baundry, have challenged this view: cinema has no genesis and no single discovery from which it sprung. The purpose of this article is to analyse these arguments in the light of the theories found in Greek philosophy.